2011
DOI: 10.1121/1.3658454
|View full text |Cite
|
Sign up to set email alerts
|

Model-based seafloor characterization employing multi-beam angular backscatter data—A comparative study with dual-frequency single beam

Abstract: Sediment geoacoustic inversion results are estimated employing a multi-beam (MB) echo-sounding system operable at 95 kHz. To characterize the western continental shelf of India (off Goa) seafloor, MB backscatter signals were acquired along with grab sediment samples. The substrate type and roughness of the site were estimated using the composite roughness scattering model with the measured backscatter values. The seafloor parameters, namely mean grain size (M(φ)); roughness spectrum strength (w(2)) and exponen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…Physically based geoacoustic models, such as the composite roughness model, have been developed to investigate the sediment‐acoustic relationship (APL‐UW, ; Fonseca et al, ; Hamilton, ; Jackson et al, ; Jackson & Briggs, ). Previous studies using these physical models demonstrated that sediment grain size properties and various substrate types can be distinguished based on their backscatter angular response curves (APL‐UW, ; Chakraborty et al, ; De & Chakraborty, ; Fonseca et al, ; Fonseca & Mayer, ; Haris et al, ). However, due to the large variability of seabed properties across the global oceans, one single geoacoustic model is not likely applicable to all cases (Hamilton, ; Hughes Clarke, ).…”
Section: Introductionmentioning
confidence: 99%
“…Physically based geoacoustic models, such as the composite roughness model, have been developed to investigate the sediment‐acoustic relationship (APL‐UW, ; Fonseca et al, ; Hamilton, ; Jackson et al, ; Jackson & Briggs, ). Previous studies using these physical models demonstrated that sediment grain size properties and various substrate types can be distinguished based on their backscatter angular response curves (APL‐UW, ; Chakraborty et al, ; De & Chakraborty, ; Fonseca et al, ; Fonseca & Mayer, ; Haris et al, ). However, due to the large variability of seabed properties across the global oceans, one single geoacoustic model is not likely applicable to all cases (Hamilton, ; Hughes Clarke, ).…”
Section: Introductionmentioning
confidence: 99%
“…The roughness power spectrum is often parameterized using a power law by slope and intercept of a linear regression line through the points of the periodogram estimate in log-log space. Indeed, the parameters γ 2 and w 2 used in the scattering models are the slope and intercept, respectively, of the 2-D roughness power spectrum, which are estimated from the 1-D power-law values (Haris et al, 2011). A wide range of 2-D roughness power spectrum parameters of the study area are available and offer an opportunity to determine their relationship with the presently estimated universal multifractal parameters.…”
Section: Comparison With Inversion Resultsmentioning
confidence: 99%
“…The numerical approach employed for extracting information from the data is commonly referred to as "inversion modeling". The inversion modeling primarily involves physics-based inversion of echosounding data to obtain the upper-layer seafloor roughness parameters, namely the sediment mean grain size (M ϕ ); spectral parameters at the water-seafloor interface (γ 2 , w 2 ); and sediment volume parameter (σ 2 ), which can be used to examine the fine scale seafloor processes (Sternlicht and de Moustier, 2003a, b;De and Chakraborty, 2011;Haris et al, 2011).…”
Section: Comparison With Inversion Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is, however, a growing demand for combining seabed classification with bathymetric surveys [1] [2] that include Multibeam Echo Sounders (MBES). Methods based on inversion of geo-acoustic properties using physics-based models [3][4][5][6] will require true sound pressure levels. Therefore, in April, 2011, RESON participated in the GulfEx with a SeaBat 7125.…”
Section: Introductionmentioning
confidence: 99%